Terrace-like morphology of the boundary created through basal-prismatic transformation in magnesium. (15th April 2015) - Liu, Bo-Yu; Wan, Liang; Wang, Jian; Ma, Evan; Shan, Zhi-Wei
Abstract : Boundaries created through basal-prismatic transformation in submicron-sized single crystal magnesium have been investigated systematically using in situ transmission electron microscopy. We found that these boundaries not only deviated significantly from the twin plane associated with { 1 0 1 ¯ 2 } twin, but also possessed a non-planar morphology. After the sample was thinned to be less than 90 nm, aberration-corrected scanning transmission electron microscopy observation found that the basic components of these boundaries are actually terrace-like basal-prismatic interfaces.